2009
DOI: 10.1002/iroh.200811123
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of Cyanobacteria and Diatoms in a Thermally Stratified Canyon‐Shaped Reservoir

Abstract: Moreno-Ostos, E., Cruz-Pizarro, L., Basanta, A., George, D. G. (2009). Spatial Heterogeneity of Cyanobacteria and Diatoms in a Thermally Stratified Canyon-Shaped Reservoir. International Review of Hydrobiology, 94(3), 245-257.Phytoplankton communities in lakes and reservoirs are seldom homogeneously distributed but usually aggregate in patches and gradients. In this study we have combined the use of in vivo spectrofluorometry and acoustic Doppler current profiling to investigate the effect of water movements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Differences in the horizontal distribution of cyanobacterial blooms within lakes have been widely reported, with wind or physicochemical conditions being important drivers [28], [29], [43]. As no horizontal differences between physicochemical parameters have been found in the past in Lake Yangebup [32], [34], wind was the most likely driver of the large differences in cyanobacterial biomass between sites in our study.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Differences in the horizontal distribution of cyanobacterial blooms within lakes have been widely reported, with wind or physicochemical conditions being important drivers [28], [29], [43]. As no horizontal differences between physicochemical parameters have been found in the past in Lake Yangebup [32], [34], wind was the most likely driver of the large differences in cyanobacterial biomass between sites in our study.…”
Section: Discussionsupporting
confidence: 44%
“…Often, blooms establish in areas that contain higher nutrient concentrations, for instance near inflows from drains, or buoyant cyanobacterial cells accumulate along shores in the downwind direction [28], [29]. This generates large spatial differences of cyanobacterial biomass within a system, leading to spatially different conditions for zooplankton communities that might translate into differences in food web structures [19].…”
Section: Introductionmentioning
confidence: 99%
“…A widely used approach is based on the detection of the fluorometric signal produced by the phytoplankton photosynthetic pigments . Based on this approach, the use of the fluorometric probe has allowed the description of the spatial heterogeneity of phytoplankton along the water column (Alexander and Imberger, 2009;Longhi and Beisner, 2009;Moreno-Ostos et al, 2006;Selmeczy et al, 2016;Serra et al, 2007) and along horizontal gradients (Carraro et al, 2012;Moreno-Ostos et al, 2009;Salcher et al, 2011). The use of these probes is particularly useful to catch short-term variations in the vertical distribution of metalimnetic species like P. rubescens due to displacement caused by seiches.…”
Section: Vertical and Horizontal Distribution Of The Microcystin Prodmentioning
confidence: 99%
“…2009). Moreno-Ostos et al (2009) found the longitudinal variation in the planktonic diatom assemblages was influenced by wind driven currents. While some studies have assessed planktonic diatom assemblages in reservoirs, an increased knowledge of regional spatial distribution of sediment surface diatoms within reservoirs is required to validate the use of diatoms as bioindicators in these environments and infer historic conditions.…”
Section: In Brazil Andmentioning
confidence: 94%
“…These 319 publications cover a wide range of topics on various aspects of diatoms, including studies on silica (Conley et al 2000, Znachor andNedoma 2008), food webs (Scharf 2008), and morphology of individual diatom species (Genkal andKiss 1993, Genkal 2012). There are numerous studies on spatial and/or temporal variability of phytoplankton (Marce et al 2007, Caputo et al 2008, Moreno-Ostos et al 2009, Rychtecky and Znachor 2011, Schneck et al 2011, Menezes et al 2013 as well more general composition of the phytoplankton assemblage (Fonseca andBicudo 2008, Zhou et al 2015). Observing changes in phytoplankton composition as a reservoir ages and shifts from diatom dominated to cyanobacteria dominated, in addition to determining trophic status from the phytoplankton community were also common themes of research.…”
Section: Diatom Research In Reservoirsmentioning
confidence: 99%